Lungs of a Chronic Smoker: The Case of Heroin-Induced Emphysema in a 35-Year-Old Man - Neil Gerts; George Ishak; Ian Joel; Jasprit Takher (Annals of Internal Medicine: Clinical Cases)
Recently, heroin has become more easily accessible, which has led to an increase in its tolerance, addiction, and misuse potential. According to several reports, among many modes of use, smoking and inhaling heroin are the most common methods of its misuse among young adults. As a result, many users younger than age 40 years are now presenting with severe airway disease. In this case report, a 35-year-old man with a history of heroin use subsequently had severe emphysema with numerous bullae. The patient reported a long-standing history of inhaling heroin vapor. A genetic work-up for alpha-1 antitrypsin deficiency was negative. Here, we raise the concern of heroin-induced bullous emphysema.